Analysis of vegetative homeostasis state of elite handball players - Prystupa, Y.N.; Tyshchenko, V.O. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: to study characteristics and dynamic of elite handball players’ physiological indicators. Material: In experiment elite handball players (n=112, age 18-35 years) participated. For determination of vegetative homeostasis state we analyzed variability of heart rhythm. The researches were conducted in laboratory conditions in rest state, in lying position during 5 minutes. Results: it was found that organism’s adaptation reactions to training loads go with different tension of regulation systems. At the end of competition period there appears hyper-kinetic syndrome. It witnessed insufficiency of means, which permit to maintain optimal regulation of cardio-vascular system and increase its functional potentials. Conclusions: indicators of cardio-vascular system and their dynamic w3itnessed maintaining of high level of handball players’ organism hemodynamic provisioning. High level of vegetative homeostasis pointed at certain degree of sportsmen’s fitness. Such state is sufficient for preservation of high potential of sympathetic -adrenaline system and overcoming of fatigue processes.